A Method for Longitudinal Prospective Evaluation of Markers for a Subsequent Event - Little, Roderick J. (Oxford University Press, 2011)
In this paper, the authors describe a simple method for making longitudinal comparisons of alternative markers of a subsequent event. The method is based on the aggregate prediction gain from knowing whether or not a marker has occurred at any particular age. An attractive feature of the method is the exact decomposition of the measure into 2 components: 1) discriminatory ability, which is the difference in the mean time to the subsequent event for individuals for whom the marker has and has not occurred, and 2) prevalence factor, which is related to the proportion of individuals who are positive for the marker at a particular age. Development of the method was motivated by a study that evaluated proposed markers of the menopausal transition, where the markers are measures based on successive menstrual cycles and the subsequent event is the final menstrual period. Here, results from application of the method to 4 alternative proposed markers of the menopausal transition are compared with previous findings.